TESTES POST-HOC: LEVANTAMENTO DE TESTES UTILIZADOS NA FITOPATOLOGIA - ROSA, Artur Guerra; BLANCO, Neder Henrique Martinez; PESSÔA, Guilherme Martins; COSTA, Brenda Fernandes; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2022)
-